Identification Physics Concept in Local Wisdom Pigeon Race on Madura Island - Umamah, Chairatul; Irawan, Fery; Kholida, S. Ida; Indahnia K, El (Universitas Muhammadiyah Makassar, 2024)
Indonesia is a rich country in local wisdom, but it is starting to fade along with technological developments. pigeons racing on Madura island is an example of local wisdom that can be used as a source of new knowledge in understanding physics concepts in social life. Pigeon racing is a big competition that is held after the rice harvest season arrives. This research aims to analyze the physics concepts contained in pigeon racing. This research was conducted using a descriptive method with a qualitative approach. data collection was obtained by technically analyzing the data subjectively using interview, observation and literature study methods. Based on data analysis and literature studies, it was found that in pigeon racing, there are physics concepts related to motion and displacement. At a rapid rate, the calculation results show, that the speed of an object can increase uniformly or decrease uniformly. An object is said to be moving in a straight line and changing uniformly to accelerate if the object's speed increases uniformly. Meanwhile, an object is said to be moving in a straight line and changes evenly and is slowed down if the object's speed decreases uniformly. The change in speed per unit time is called acceleration. Then, The results of this research can be used as a contextual learning resource in high school physics subjects about motion.